Effects of nitrogen fertilizer application rate and time to first harvest on leaf area index; leaf nitrate content and yield of irrigated leaf rape (Brassica napus L. var. Giant) - Masaka, J.; Chandiposha, M.; Makaure, B. T.; Mazina, B. (International Journal of Horticultural Science, 2021)
In Zimbabwe, smallholder cultivation of leaf rape is of considerable importance due to the increasing demand for the leaf vegetable from the rapidly increasing urban populations.  A two-season field trial was conducted in the Agricultural Practice Experimental Plots of the Midlands State University in central Zimbabwe. The objective of the study was to establish selected biometric responses of leaf rape to N fertilizer rates and time to first harvesting. Increasing the rate of N fertilizer application considerably improves the yield of fresh rape leaf; LAI and concentration of leaf nitrate. Delaying rape leaf harvest after N fertilizer side dressing can be used as a strategy to boost rape leaf yield for vegetable markets with high single delivery demand. When harvesting is deliberately delayed after N fertilizer application rape LAI are significantly increased. Delaying the first leaf harvests by 7; 14 and 21 days after N fertilizer side dressing amendments increases the content of nitrate in fresh rape leaves. Fresh rape yield can be more accurately predicted by values of rape LAI. Nitrate concentrations in fresh rape leaf is a poor predictor of rape yield under field conditions.